Teaching teamwork and collaboration: A task-centered clinical design - Morrill, Deborah (Nurse education today, 2018)
Keywords: dept.nur

Clinical Case Studies for the Family Nurse Practitioner - Neal-Boylan, Leslie (Wiley-Blackwell, 2011)
Keywords: Case studies; Case studies; Nurse practitioners; Family nursing; dept.nur; faculty_collection

Clinical Case Studies in Home Health Care - Neal-Boylan, Leslie (Wiley-Blackwell, 2011)
Keywords: Case studies; Home care services; dept.nur

Legal Resource for School Health Services - Resha, Cheryl A.; Taliaferro, Vicki (SchoolNurse.com, 2017)
A reference regarding legal issues impacting school health. The book provides information on over 50 topics that school health services programs and school nurses encounter, addresses legal implications and presents legal resources and references that can be applied to practice and policy development. - Cover
Keywords: Law and legislation; School nursing; United States; dept.nur; faculty_collection

School Nurse Resource Manual: A Guide to Practice - Taliaferro, Vicki; Resha, Cheryl A. (School Health Alert, 2017)
School nurses' work focuses directly on three areas: health services, health education, and the school environment. Their services require diverse knowledge including, but not limited to, pediatric/adolescent health, infectious diseases, mental health, chronic diseases, and emergency care. They can influence health and safety aspects of schools and can provide leadership to a district's or campus' coordinated school health program that in addition to health services, health education, and the school environment addresses mental health and social services, nutrition services, physical activity, family and community involvement, and/or staff health promotion. This work is written for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidence-based policies and procedures for safe student care.
Keywords: Handbooks; manuals; etc; School Nursing; School nursing; dept.nur; faculty_collection

Essentials of nursing law and ethics - Westrick, Susan J. (Jones & Bartlett Learning, 2014)
Keywords: Law and legislation; Nursing ethics; Nursing; United States; dept.nur; faculty_collection

Sabbatical leave report: sabbatical Fall 2012 / submitted by: Susan J. Westrick, Professor, Department of Nursing. - Westrick, Susan J. (2012)
This sabbatical project involved re-writing as the sole author a previously co-authored textbook, Essentials of Nursing Law and Ethics (2009), devoted to traditional and contemporary legal and ethical concerns for nursing students and practicing nurses.
Keywords: dept.nur; faculty_collection; sabbatical_report

Abdominal pain - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Aching in legs - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Burning epigastric pain after meals - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Clinical case studies for the family nurse practitioner - Neal-Boylan, L. (wiley, 2011)
Clinical Case Studies for the Family Nurse Practitioner is a key resource for advanced practice nurses and graduate students seeking to test their skills in assessing, diagnosing, and managing cases in family and primary care. Composed of more than 70 cases ranging from common to unique, the book compiles years of experience from experts in the field. It is organized chronologically, presenting cases from neonatal to geriatric care in a standard approach built on the SOAP format. This includes differential diagnosis and a series of critical thinking questions ideal for self-assessment or classroom use. © 2011 by John Wiley & Sons, Inc.
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner Pages: 404 Publication Title: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Contraception - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Facial pain - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Fatigue and joint pain - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Headache - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Insomnia - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Introduction - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Keywords: dept.nur; ⛔ No DOI found

Knee pain - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Muscle tenderness - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Urinary frequency - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Vaginal itching - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Wrist pain and swelling - Neal-Boylan, L. (Clinical Case Studies for the Family Nurse Practitioner, 2011)
Journal Abbreviation: Clinical Case Studies for the Family Nurse Practitioner
Keywords: dept.nur

Clinical Case Studies in Home Health Care - Neal-Boylan, L. (Wiley Blackwell, 2013)
Home health care is an important aspect of community health and a growing area of healthcare services. Clinical Case Studies in Home Health Care uses a case-based approach to provide home healthcare professionals, educators, and students with a useful tool for thoughtful, holistic care. The book begins with a thorough and accessible introduction to the principles of home health care, including a discussion of supporting theoretical frameworks and information on managing complexities, transitioning patients to home care, and preparation for the home visit. Subsequent sections are comprised entirely of case studies organized by body system. Though cases are diverse in content, each is presented in a consistent manner, incorporating relevant data about the patient and caregivers and the approach to patient care and promoting a logical approach to patient presentation. Cases also include helpful tips about reimbursement practices, cultural competence, community resources, and rehabilitation needs. © 2011 by John Wiley & Sons, Inc.
Journal Abbreviation: Clin. Case Stud. in Home Health Care Pages: 485 Publication Title: Clin. Case Stud. in Home Health Care
Keywords: dept.nur

Multiple Sclerosis - Neal-Boylan, L. (Clinical Case Studies in Home Health Care, 2013)
Journal Abbreviation: Clin. Case Stud. in Home Health Care
Keywords: dept.nur

Theoretical Frameworks That Support Home Care - Neal-Boylan, L. (Clinical Case Studies in Home Health Care, 2013)
Journal Abbreviation: Clin. Case Stud. in Home Health Care
Keywords: dept.nur

Case Studies in Gerontological Nursing for the Advanced Practice Nurse - Kazer, M.W.; Neal-Boylan, L. (Wiley Blackwell, 2011)
As the fastest growing population sector worldwide, older adults are seen in almost every care setting in which clinicians practice. Developed as a resource for advanced practice nurses in any setting, Case Studies in Gerontological Nursing for the Advanced Practice Nurse presents readers with a range of both typical and atypical cases from real clinical scenarios. The book is organized into six units covering cases related to ageism, common health challenges, health promotion, environments of care, cognitive and psychological issues, and issues relating to aging and independence. Each case follows a similar format including the patient's presentation, critical thinking questions, and a thorough discussion of the case resolution through which students and clinicians can enhance their clinical reasoning skills. Designed to promote geriatric clinical education through self-assessment or classroom use, Case Studies in Gerontological Nursing for the Advanced Practice Nurse is a key resource for all those dedicated to improving care for older adults. © 2012 by John Wiley & Sons, Inc. All rights reserved.
Journal Abbreviation: Case Stud. in Gerontol. Nurs. for the Adv. Pract. Nurse Pages: 398 Publication Title: Case Stud. in Gerontol. Nurs. for the Adv. Pract. Nurse
Keywords: dept.nur

Introduction - Case Studies in Gerontological Nursing for the Advanced Practice Nurse - Kazer, M.W.; Neal-Boylan, L. (Case Studies in Gerontological Nursing for the Advanced Practice Nurse, 2011)
Keywords: dept.nur

Are You in the Hospital Again? - Lacey, K.O. (Case Studies in Gerontological Nursing for the Advanced Practice Nurse, 2011)
Journal Abbreviation: Case Stud. in Gerontol. Nurs. for the Adv. Pract. Nurse
Keywords: dept.nur

NLN's simulation leaders give SIRC bibliography site a Makeover - Alfes, C.M.; Aronson, B.; Bethards, M.L.; Chesney, T.; De Luna, R.; Newton, R.; Weaver, A. (Nursing Education Perspectives, 2014)
0 citations (Crossref) [2023-10-31]
Keywords: Databases; Bibliographic; Health Information Management; Humans; Internet; Models; Educational; Patient Simulation; Societies; Nursing; United States; article; bibliographic database; dept.nur; educational model; human; medical information system; nursing organization; organization and management; peer-reviewed; teaching

The knowledge patients impart - Green, C.A. (Clinical Journal of Oncology Nursing, 2014)
0 citations (Crossref) [2023-10-31]
Keywords: Death; Humans; Knowledge; Nurse-Patient Relations; Patients; dept.nur; human; knowledge; nurse patient relationship; patient

Nursing Students' Use of Electronic and Social Media: Law, Ethics, and E-Professionalism - Westrick, S.J. (Nursing Education Perspectives, 2016)
AIM This article discusses the promotion of professionalism in nursing students with regard to the use of electronic and social media. BACKGROUND Misuse of social media can lead to disciplinary actions and program dismissal for students and to legal actions and lawsuits for nursing programs. Programs are concerned about breaches of patient confidentiality and release of private or inappropriate information that jeopardizes clinical placements and relationships. METHOD The American Nurses Association Code of Ethics and National Council of State Boards of Nursing social media guidelines provide a foundation for promoting e-professionalism in students. Recent law cases involving students who were dismissed from nursing programs due to social media misuse are analyzed. CONCLUSION Schools need policies that clearly establish expectations and the consequences of misuse of social media platforms. Lessons learned from the legal cases presented provide further guidance for both nursing students and nursing programs. © 2016 Lippincott Williams & Wilkins.
31 citations (Crossref) [2023-10-31]
Keywords: Attitude to Computers; Confidentiality; Guidelines as Topic; Humans; Legal and Ethical Issues; Nursing Education; Nursing Students; Professionalism; Social Media; Social Media Policy; Students; Nursing; United States; attitude to computers; confidentiality; dept.nur; ethics; expectation; human; human experiment; law suit; legislation and jurisprudence; nursing education; nursing organization; nursing student; peer-reviewed; practice guideline; professionalism; psychology; social media; standards

Performing pediatric eye exams in primary care - Martin, E.F. (Nurse Practitioner, 2017)
Early vision care is critical for all children. If undetected, eye disorders such as amblyopia and strabismus may result in permanent vision loss. Vision exams should include a careful history and physical including fix and follow, red reflex, and cover/uncover testing. Photo screening and visual acuity exams should be administered whenever possible. © 2017 Wolters Kluwer Health, Inc. All rights reserved.
1 citations (Crossref) [2023-10-31]
Keywords: Adolescent; Child; Child; Preschool; Eye Diseases; Humans; Infant; Infant; Newborn; Physical Examination; Primary Health Care; Vision Screening; adolescent; amblyopia; child; children; dept.nur; eye disease; eye exam; human; infant; newborn; nursing; pediatric patients; peer-reviewed; physical examination; preschool child; primary health care; strabismus; vision exam; vision test; well-child exam

Make America wait again - Petrovic, K. (Journal of International Women's Studies, 2017)
As a means of redirecting my own personal grief that stemmed from Hillary Rodham Clinton's loss to Donald J. Trump in the most recent presidential election, I penned the following prose during the early morning hours of November 9, 2016 as Trump gave his victory speech. Like many Americans who voted in the 2016 Presidential Election, I support the right to vote for one's choice of presidential candidate; however, I am not alone in my concerns about the current presidential administration. Not only are Trump's attempts to silence the media and the right to freedom of speech cause for alarm, but his ideas on healthcare, human rights and international political relationships arguably contribute to apprehension and unease for any number of people. No presidency is without its issues, but the verse penned here may speak to others as the Trump presidency continues to unfold. © 2017 Journal of International Women's Studies.
Keywords: Donald trump; Hillary rodham clinton; United States of America; Woman president; dept.nur; ⛔ No DOI found

The benefits of taekwondo training for undergraduate students: A phenomenological study - Petrovic, K. (Societies, 2017)
The purpose of this phenomenological research was to discover whether training in the Korean martial art of Taekwondo may benefit undergraduate (UG) students in handling stress. The goal of this innovative approach to learning and stress management was to allow UG students from across disciplines at a metropolitan university achieve an increased sense of emotional balance, inner peace, and overall well-being in body, mind, and spirit. No such study has been conducted before now. This research was multidisciplinary in its inclusion of insights from the tenets of higher education, human development and psychology, nursing and sociology, as well as the art, philosophy, and sport of Taekwondo. Ten UG student participants were sought for this research study, though a total of eight students agreed to participate. The study was open to all of the UG students at this university. Phenomenology was used to identify themes that emerged regarding student participant’s experience with stress. Consequently, new ideas were established about the ways in which UG students learned to use Taekwondo training to overcome stress, thereby improving upon and maintaining health and well-being in body, mind, and spirit. © 2017 by the author; licensee MDPI, Basel, Switzerland.
13 citations (Crossref) [2023-10-31]
Keywords: Higher education; Holistic health; Human development; Stress; Taekwondo; Undergraduate students; dept.nur

Examining changes to statewide NP practice in Connecticut - Kazer, M.W.; O'Sullivan, C.K.; Leonard, M. (Nurse Practitioner, 2018)
In 2014, Connecticut legislators eliminated the need for advanced practice registered nurses with 2,000 practice hours to obtain collaborative practice agreements with physicians. This study examined resulting practice changes, barriers, and suggestions for improved implementation of independent practice. Thirteen NPs participated in focus groups to share their experiences and recommendations. © 2018 Wolters Kluwer Health, Inc. All rights reserved.
2 citations (Crossref) [2023-10-31]
Keywords: APRNs; Advanced practice registered nurses; Collaborative practice agreements; Connecticut; Female; Focus Groups; Full-practice authority; Humans; Independent practice; Male; Middle Aged; Nurse Practitioners; Practice Patterns; Nurses'; article; dept.nur; female; human; information processing; legislation and jurisprudence; male; middle aged; nurse practitioner; nursing practice; peer-reviewed; psychology; registered nurse

Urticaria multiforme: A case study - Maynard, K. (Journal of the Dermatology Nurses' Association, 2018)
Urticaria multiforme is a rare, hypersensitivity reaction that occurs in infants and small children. Because of its rare occurrence, many providers are unable to accurately identify the rash and associated symptoms to unnecessary laboratory and histological testing or misdiagnosis. This article highlights the case of an 11-month-old female infant with urticaria multiforme. It explores the identification, diagnosis, and current treatment recommendations. © 2018 Dermatology Nurses' Association.
2 citations (Crossref) [2023-10-31]
Keywords: Article; Hypersensitivity Reaction; Pediatric Rash; Urticaria Multiforme; amoxicillin; amoxicillin plus clavulanic acid; anamnesis; antibiotic therapy; case report; cefdinir; cetirizine; clinical article; dept.nur; diphenhydramine; face edema; female; foot edema; hand edema; human; infant; otitis media; papule; peer-reviewed; physical examination; priority journal; pruritus; rash; urticaria multiforme

Implementing post-discharge 48-hour scripted call for patients with heart failure: An evidence-based practice quality improvement project - Ruggiri, J.C.; Milner, K.A.; Buonocore, D. (MEDSURG Nursing, 2019)
Post-discharge call programs are a simple and effective way to identify and intervene for patient care issues that may occur after discharge. Nurses play a key role in these programs and can lead quality improvement projects on their units to improve patient care during the transition from hospital to home. © 2019, Anthony J. Jannetti Publications, Inc.. All rights reserved.
Keywords: dept.nur; peer-reviewed; ⛔ No DOI found

Review: Depressive symptoms and fatigue as mediators of relationship between poor sleep factors and medication adherence in HIV-positive women. - Petrovic, Kimberly (Journal of Research in Nursing, 2015)
0 citations (Crossref) [2023-10-31] Place: (C)2015Sage Publications
Keywords: dept.nur

Calm in Chaos: Prose on Tensions of Hate and Distrust in Society - Green, Cheryl; Green, Joshua William (Westbow Press, 2019)
Keywords: Hate; Poetry; Poetry; Racism; dept.nur; faculty_collection

Facilitating trust engenderment in secondary school nurse interactions with students. - Summach, Anne H J (The Journal of school nursing : the official publication of the National Association of School Nurses, 2011)
School nurses are involved in a complex framework of interactions with students, other professionals, parents, and administrators. Trust between nurse and student is critical for interaction effectiveness. The goal of this study was to understand through phenomenology the process of engendering trust in school nurse-high school student interactions. The qualitative approach explored school nurse perceptions of experiences interacting with students, yielding insights into nurse- and setting-based factors contributing to the development of trust. Subthemes within these included key behaviors and attributes enhancing trust engenderment in school nurse-student interactions. Study findings were well supported by the existing nursing and psychological research literature. Nurses that purposefully strive to develop trust in young people will maximize adolescent health results.
11 citations (Crossref) [2023-10-31] Place: United States Summach, Anne H J. Southern Connecticut State University, New Haven, CT, USA.
Keywords: *Nurse-Patient Relations; *Schools/sn [Statistics & Numerical Data]; *Students/px [Psychology]; *Trust/px [Psychology]; Adolescent; Adolescent Behavior; Adult; Clinical Competence; Humans; Nurse-Patient Relations; Patient Satisfaction; Qualitative Research; Schools; Students; Trust; Young Adult; adolescent; adult; article; child behavior; clinical competence; dept.nur; high school; human; nurse patient relationship; patient satisfaction; psychological aspect; qualitative research; role promotion/development; school; school nurse characteristics; school nurse knowledge/perceptions/self-efficacy; statistics; student; trust

Improving sleep-wake disturbances in patients with cancer - Lamberti, Mary Patricia (Clinical Journal of Oncology Nursing, 2014)
Patients with cancer tend to suffer sleep-wake disturbances at a higher rate than the general population. Insomnia and fatigue should be regarded as a significant patient safety issue, as poor sleep can elevate patients' risks of falls, motor vehicle accidents, and acute infectious illnesses. To alleviate those risks, oncology nurses should be familiar with effective evidence-based practices for assessing and improving patients' sleep quality.
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/007-927-422-564-577 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Accidental Falls; Accidents; Traffic; Cancer; Humans; Infection; Interventions; Neoplasms; Patient Safety; Safety; Sleep; Sleep Wake Disorders; complication; dept.nur; falling; human; infection; neoplasm; patient safety; traffic accident

Gaming the system: developing an educational game for securing principles of arterial blood gases - Boyd, Cory Ann; Warren, Jonah; Glendon, Mary Ann (Journal of Professional Nursing, 2016)
This article describes the development process for creating a digital educational mini game prototype designed to provide practice opportunities for learning fundamental principles of arterial blood gases. Mini games generally take less than an hour to play and focus on specific subject matter. An interdisciplinary team of faculty from two universities mentored student game developers to design a digital educational mini game prototype. Sixteen accelerated bachelor of science in nursing students collaborated with game development students and playtested the game prototype during the last semester of their senior year in nursing school. Playtesting is a form of feedback that supports an iterative design process that is critical to game development. A 10-question survey was coupled with group discussions addressing five broad themes of an archetypical digital educational mini game to yield feedback on game design, play, and content. Four rounds of playtesting and incorporating feedback supported the iterative process. Accelerated bachelor of science in nursing student playtester feedback suggests that the digital educational mini game prototype has potential for offering an engaging, playful game experience that will support securing the fundamental principles of arterial blood gases. Next steps are to test the digital educational mini game for teaching and learning effectiveness. (C) 2016 Elsevier Inc. All rights reserved.
4 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/002-463-666-213-787 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Arterial blood gases; Educational digital games; Interdisciplinary collaboration; Mini games; Nursing students; Serious games; arterial blood; blood gas; clinical article; dept.nur; human; learning; nursing education; nursing student; teaching

Enhancing student nurse learning through participation in a community-based educational program for children and families - Krol, Maria; Resha, Cheryl; Glendon, Mary Ann (Journal of Community Health Nursing, 2016)
Health disparities, especially among minorities, persist; obesity is a national concern; and the combined effect can be significant for families and populations. In an effort to address obesity at an early age, the National Association of Hispanic Nurses (NAHN), developed the Muevete USA project. Muevete USA (from the Spanish verb for to move) features five lesson plans on healthy lifestyles for children and their families. This article describes Muevete USA, the partnership with a local school of nursing, the implementation of the program at the local level and the emerging program and student outcomes of a successful partnership.
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/051-475-177-637-576 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Child; Child Health; Community-Based Participatory Research; Humans; Obesity; Schools; Students; Nursing; child; child health; dept.nur; human; nursing student; obesity; participatory research; school

Using Schools of Nursing to Help Fill the Gap - Resha, Cheryl (NASN School Nurse, 2016)
The shortage of school nurses, school nurses covering multiple buildings, and the expanded role of the school nurse has called for innovative ideas to meet the growing health care needs of youth. Partnering with local schools of nursing may be a welcomed strategy. This brief article will share the benefits of hosting student nurses as well as identify ways to begin these partnerships. © 2016 The Author(s).
3 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-767-614-188-699 tex.type: [object Object]
Keywords: Adult; Curriculum; Education; Nursing; Baccalaureate; Female; Humans; Interprofessional Relations; Male; Middle Aged; Organizational Innovation; School Health Services; School Nursing; Schools; Nursing; Students; Nursing; United States; adult; curriculum; dept.nur; education; female; health promotion; human; male; middle aged; nursing education; nursing student; organization; organization and management; partnerships; public relations; school health nursing; school health service; schools of nursing; student nurses

Predictors of types of caregiver burden - Unson, Christine; Flynn, Deborah; Haymes, Elayne; Sancho, Diane; Glendon, Mary Ann (Social Work in Mental Health, 2016)
This study identified the types of caregiver stress and the caregiver and care management characteristics that are associated with this stress. 169 caregivers were recruited from a variety of community settings that cater to caregivers in a New England metropolitan area. They completed the Zarit Burden Interview (ZBI) and a questionnaire concerning their care recipient and caregiving arrangements. Principal Components Analysis on the ZBI resulted in five factors: personal strain/loss, uncertainty/inadequacy, social strain/embarrassment, anger, and dependency. The average age of the caregiver was 59.95 years (SD = 11.75) and the average age of the CR was 83.44 years (SD = 7.88). Of the 169 caregivers, 82% were women, 61.5% daughters/in-law or wives (12.9%), 34.3% were solo caregivers; 16.8% little or no burden, 39.9% reported mild to moderate burden, 35% moderate to severe burden, and 8.4% had severe burden. Dependency (22.4%) and personal strain/loss (13.7%) had the highest proportions reported as “often” to “nearly always.” The ZBI was predicted by only two caregiver characteristics, indicating that it is not sensitive to the experiences of different types of caregivers. Caregivers experience different types of burden depending on their gender, kinship roles, and levels of involvement in the care of their older relative. Solo caregiver status and age (younger) significantly predicted most if not all 5 burden types. Solo and young caregivers experienced the highest levels of caregiver burden. Social work practice must identify the caregiver’s life stage and other and self-expectations in relation to dependency, personal loss, embarrassment, anger, or uncertainty. © 2016 Taylor & Francis.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/052-743-882-854-036 tex.type: [object Object]
Keywords: Caregiver burden; United States; adult; aged; anger; caregiver burden; controlled study; dependency; dept.nur; dept.pch; expectation; female; gender; human; human experiment; interview; male; principal component analysis; questionnaire; recipient; social work practice; strain; uncertainty

Effectiveness of a role-modeling intervention on student nurse simulation competency - Aronson, Barbara; Glynn, Barbara; Squires, Timothy (Clinical Simulation in Nursing, 2013)
Novice nurses are often inadequately prepared to respond to complex, patient care situations where patients' conditions deteriorate. Exposure to a video-taped intervention that role-models and reinforces expected behavior of an expert nurse before participation in a simulation may improve student nurse performance in a cost-effective manner. The primary purpose of this quasi-experimental pre-test, post-test study was to assess the preliminary effectiveness of a theory based role-modeling intervention on enhancing student nurse competency in responding to a simulated response to rescue event. Performance was measured by a previously validated Heart Failure Simulation Competency Evaluation Tool (c) (HFSCET). Total mean scores on the HFSCET for the pre-test (59.08) and post-test (87.08) were significantly different (p = .000); students performed better on the post-test after exposure to the role-modeling intervention. A power analysis indicated a large effect size (effect size = .926; alpha = 0.50; power = 0.991). Students who had a greater number of days between the intervention and the post-test had a lower score. This innovative intervention based on established learning theory may change the way educators prepare novice students to achieve expected clinical competencies in graded simulation performance assessments. (c) 2013 International Nursing Association for Clinical Simulation and Learning. Published by Elsevier Inc. All rights reserved.
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/003-811-864-193-208 tex.type: [object Object]
Keywords: Intervention; Nursing students; Performance assessment; Simulation; dept.nur

Competency assessment in simulated response to rescue events - Aronson, Barbara; Glynn, Barbara; Squires, Timothy (Clinical Simulation in Nursing, 2012)
Background: Reliable and valid instruments are needed to assess patient safety competencies, specifically nursing students' ability to appropriately respond to simulated rescue events. Methods: This was an instrument development study conducted with 152 senior nursing students in 2 phases. Results: Student groups performed poorly during the simulation scenario, with mean scores on the Heart Failure Simulation Competency Evaluation Tool ranging from 46% to 56%. Interrater reliability increased to .839 after item revision during Phase 2 of the study. Discussion: This simulation competency assessment package is ready to be tested with more diverse student groups and novice nurses in the practice setting. © 2012 International Nursing Association for Clinical Simulation and Learning.
7 citations (Crossref) [2023-10-31] Citation Key Alias: pop00146 tex.type: [object Object]
Keywords: Failure to rescue; Instrument development; Nursing students; Patient safety; Simulation; dept.nur

Nurse practitioners in home health care: an update - Neal‐Boylan, Leslie; Mager, Diana; Kazer, Meredith Wallace (Home Health Care Management & Practice, 2012)
Nurse practitioners are playing an increasingly visible role in home care. The Institute of Medicine in collaboration with the Robert Wood Johnson Foundation recommends wider use of Advanced Practice Registered Nurses and there has been growing interest in using the role in home care.1 However, the physician remains the provider who must sign home health agency paperwork and orders. The "Home Health Care Planning Improvement Act" would allow nurse practitioners to certify Medicare-sponsored treatment plans.2 This article will discuss the status of the nurse practitioner role in home care, the impact of reimbursement on home care services, how the passage of the new act would change current practice, and a vision for the future role of the nurse practitioner in home health care. © 2012 SAGE Publications.
6 citations (Crossref) [2023-10-31] Citation Key Alias: pop00276 tex.type: [object Object]
Keywords: Home Health Care Improvement Act; conceptual model; dept.nur; home health care; nurse practitioner; transitional care model

An exploration and comparison of the worklife experiences of registered nurses and physicians with permanent physical and/or sensory disabilities. - Neal-Boylan, Leslie (Rehabilitation nursing : the official journal of the Association of Rehabilitation Nurses, 2012)
PURPOSE: To examine the worklife experiences of physicians, to further the exploration of the worklife experiences of nurses with disabilities, and to discover how the two healthcare professions compare with each other with regard to these experiences., METHODS: This study employed the research tradition of interpretive naturalistic inquiry and used constant comparative analysis to collect and analyze the data., FINDINGS: Despite the cultural and educational differences between physicians and RNs, their experiences as healthcare professionals with self-identified permanent physical and/or sensory disabilities were very similar. The research team identified five core themes., CONCLUSIONS: Healthcare professionals, including staff and administrators, need to make an effort to retain employees as turnover and predicted shortages are likely to jeopardize the current healthcare system., CLINICAL RELEVANCE: Modifications can be made within both professions to support people with disabilities and to enable them to contribute to their professions using their abilities to think critically, solve problems, and care for patients safely. Copyright © 2012 Association of Rehabilitation Nurses.
17 citations (Crossref) [2023-10-31] Place: United States Neal-Boylan, Leslie. Department of Nursing, Southern Connecticut State University, New Haven, CT, USA. leslie.neal-boylan@yale.edu
Keywords: *Disabled Persons/rh [Rehabilitation]; *Employment; *Nurses; *Physicians; Adult; Aged; Aged; 80 and over; Career Choice; Disability; Disabled Persons; Disclosure; Emotions; Employment; Female; Humans; Male; Middle Aged; Nurse; Nurse workforce; Nurses; Patient Safety; Physician; Physicians; United States; Work life; adult; aged; article; comparative study; decision making; dept.nur; disabled person; emotion; employment; female; human; interpersonal communication; male; middle aged; nurse; patient safety; physician

The career trajectories of health care professionals practicing with permanent disabilities. - Neal-Boylan, Leslie; Hopkins, Amy; Skeete, Rachel; Hartmann, Sarah B; Iezzoni, Lisa I; Nunez-Smith, Marcella (Academic medicine : journal of the Association of American Medical Colleges, 2012)
PURPOSE: The authors sought to generate insights and hypotheses about the professional experiences of registered nurses and physicians with self-identified disabilities to inform local and national policy conversations on supporting a diverse health care workforce., METHOD: In 2009-2010, the authors conducted in-depth interviews in person and over the telephone with a sample of licensed registered nurses and physicians across the country who self-identified as having a permanent disability. They coded the interview transcripts to identify key themes across the participants' responses., RESULTS: The authors interviewed 10 registered nurses and 10 physicians. Five novel and consistent themes emerged from the data analysis: (1) Living and working with a physical/sensory disability narrows the career choices and trajectories of nurses and physicians, (2) nurses and physicians struggle with decisions regarding whether to disclose and discuss their disabilities at work, (3) nurses and physicians rarely seek legally guaranteed workplace accommodations, instead viewing patient safety as a personal responsibility, (4) interpersonal interactions often reflect the institutional climate and set the tone for how welcome nurses and physicians feel at work, and (5) reactions to workplace disability-related challenges run an emotional spectrum from anger and grief to resilience and optimism., CONCLUSIONS: The responses revealed several missed opportunities for supporting health care professionals with disabilities in the workplace. These findings should inform the continuing debate regarding what defines "reasonable accommodation" and how to create a workplace that is welcoming for nurses and physicians with disabilities.
24 citations (Crossref) [2023-10-31] Place: United States Neal-Boylan, Leslie. Department of Nursing, Southern Connecticut State University, New Haven, USA.
Keywords: *Attitude of Health Personnel; *Career Choice; *Disabled Persons/px [Psychology]; *Nurses/px [Psychology]; *Physicians/px [Psychology]; Adult; Aged; Aged; 80 and over; Female; Health Personnel; Humans; Interprofessional Relations; Interviews as Topic; Male; Middle Aged; Truth Disclosure; United States; Workplace/px [Psychology]; dept.nur

Nurses with sensory disabilities: their perceptions and characteristics. - Neal-Boylan, Leslie; Fennie, Kristopher; Baldauf-Wagner, Sara (Rehabilitation nursing : the official journal of the Association of Rehabilitation Nurses, 2011)
A survey design was used to explore the perceptions and characteristics of registered nurses (RNs) with sensory disabilities and their risk for leaving their jobs. An earlier study found that nurses with disabilities are leaving nursing and that employers do not appear to support these nurses. Work instability and the mismatch between a nurse's perceptions of his or her ability and the demands of their work increase risk for job retention problems. This study's convenience sample of U.S. RNs had hearing, vision, or communication disabilities. Participants completed a demographic form, three U.S. Census questions, and the Nurse-Work Instability Survey. Hospital nurses were three times more likely to be at risk for retention problems. Nurses with hearing disabilities were frustrated at work. Hearing difficulties increased with years spent working as a nurse. Many nurses with sensory disabilities have left nursing. Early intervention may prevent work instability and increase retention, and rehabilitation nurses are ideally positioned to lead early intervention programs.
10 citations (Crossref) [2023-10-31] Place: United States Neal-Boylan, Leslie. Southern Connecticut State University, New Haven, CT, USA. nealboylanL1@southernct.edu
Keywords: *Communication Disorders; *Disabled Persons; *Employment; *Nursing Staff; *Personnel Management; *Sensation Disorders; Adult; Aged; Communication Disorders; Communication Disorders/rh [Rehabilitation]; Disability; Disability Evaluation; Disabled Persons; Disabled Persons/rh [Rehabilitation]; Employment; Hearing Impaired Persons; Humans; Middle Aged; Nursing Staff; Nursing Staff; Hospital; Nursing shortage; Personnel Management; Persons With Hearing Impairments/rh [Rehabilitation]; Rehabilitation Nursing; Sensation Disorders; Sensation Disorders/rh [Rehabilitation]; United States; Visually Impaired Persons; Visually Impaired Persons/rh [Rehabilitation]; Workforces; adult; aged; article; communication disorder; dept.nur; disability; disabled person; employment; human; middle aged; nursing staff; patient; personnel management; rehabilitation nursing; sensory dysfunction

Dementia and Caregiver Stress: An Application of the Reconceptualized Uncertainty in Illness Theory. - Unson, Christine; Flynn, Deborah; Glendon, Mary Ann; Haymes, Elayne; Sancho, Diane (Issues in mental health nursing, 2015)
The Reconceptualized Uncertainty in Illness Theory (RUIT) was used to investigate antecedents to, appraisals of, and ways of coping with stressful caregiving. Four focus groups with caregivers (8 males and 16 females) of relatives with dementia were conducted; 15 cared for their parents and the remainder cared for their spouses. They were recruited from an adult care center and other community settings in a metropolitan area in New England. The discussions were audiotaped and transcribed verbatim. Two researchers independently coded the transcripts. Thematic analysis was structured according to the RUIT. The study is unique in its application to caregivers as opposed to patients and to all of the elements of the RUIT. Caregivers experience uncertainty in similar ways to patients with life-altering illness. Symptom severity–lack of personal boundaries, repetitive and aggressive behaviors, and the need for constant care–was the most frequent source of stress. The appraisals were mostly negative and included feelings of resentment, a lack of support from family members, financial strains, and loss of freedom. Self-improvement and self-care were important aspects of coping. Spirituality and humor were other coping skills that respondents used. Not all respondents said they were coping and some also reported that support from health care providers was not always helpful. Nurses can help improve coping by explaining the factors that contribute to caregiver strain and uncertainty, and by assisting caregivers to anticipate the effects of the caregiving role.
16 citations (Crossref) [2023-10-31] Place: England Unson, Christine. Southern Connecticut State University, Department of Public Health, New Haven, Connecticut, USA.
Keywords: *Adaptation; Psychological; *Caregivers/px [Psychology]; *Dementia/px [Psychology]; *Stress; Psychological/pc [Prevention & Control]; *Uncertainty; Adaptation; Psychological; Adult; Aged; Aged; 80 and over; Caregivers; Dementia; Dementia/th [Therapy]; Female; Humans; Male; Middle Aged; Models; Psychological; Narration; Stress; Psychological; Stress; Psychological/et [Etiology]; Uncertainty; adaptive behavior; adult; aged; caregiver; dementia; dept.nur; dept.pch; etiology; female; human; male; mental stress; middle aged; peer-reviewed; prevention and control; psychological model; psychology; uncertainty; verbal communication; very elderly

Scope and standards of practice - Resha, Cheryl Ann (School Nursing: A Comprehensive Text, 2019)
Produced in cooperation with the National Association of School Nurses, this text includes comprehensive coverage of the multiple facets of school nursing—from the foundations of practice and the roles and functions of a school nurse through episodic and chronic illness and behavioral issues, to legal issues and leading and managing within school settings. Written and edited by school nurses and pediatric experts, it features real-world-tested, best practices based on evidence and experience. There’s content here that you won’t find in other books, such as health assessments, individualized health plan development, mental health conditions including adolescent depression, contemporary legal issues, and current policy statements essential to school nursing.
Google-Books-ID: VXWmDwAAQBAJ
Keywords: Medical / Nursing / General; dept.nur

Fibromyalgia treatment and management considerations for nurse practitioners - Stournaras, Dana; Petrovic, Kimberly (Journal of the American Association of Nurse Practitioners, 2019)
The purpose of this case study is to examine the role of the nurse practitioner in the management and treatment of a 35-year-old female patient diagnosed with several conditions, including fibromyalgia posttraumatic stress disorder, anxiety, and depression. Fibromyalgia is a chronic, nonprogressive rheumatic condition with cardinal symptoms of widespread pain and fatigue; it affects more than 5 million people in the United States. This case study examines the nurse practitioner's role in managing fibromyalgia. Benzodiazepines and opioids may be prescribed for treatment of symptoms but prove ineffective, thus contributing to dependency issues. Controversy exists over classification of fibromyalgia as a rheumatologic condition versus a mental health disorder. Fibromyalgia frequently is accompanied by anxiety and depression, making this illness difficult to diagnose and treat.
2 citations (Crossref) [2023-10-31] tex.eissn: 2327-6924 tex.unique-id: ISI:000480702800008
Keywords: Adult; Anxiety; Depression; Female; Fibromyalgia; Humans; Nurse Practitioners; Practice Patterns; Nurses'; Stress Disorders; Post-Traumatic; Treatment Outcome; adult; advanced practice nursing; anxiety; benzodiazepines; chronic disease; depression; dept.nur; female; fibromyalgia; hearing loss; human; nurse practitioner; nurse practitioners; nursing practice; opioids; pain; pathophysiology; peer-reviewed; posttraumatic stress disorder; psychology; role; role concept; treatment outcome

International board certified lactation consultants’ practices regarding supplemental feeding methods for breastfed infants - Penny, Frances; Judge, Michelle P.; Brownell, Elizabeth A.; McGrath, Jacqueline M. (Journal of Human Lactation, 2019)
Background: According to the Baby Friendly Hospital Initiative, when supplementary feeding occurs, mothers should be counseled on the use and risks of feeding bottles and teats. To help support this initiative it is important to understand the supplementation practices of Internationally Board Certified Lactation Consultants (IBCLC)®. Research aims: To determine (1) if the location of an IBCLC’s practice has any impact on supplemental feeding methods; (2) the preferred methods of and the main reasons for supplementation; (3) the level of an IBCLC’s confidence with supplemental feeding methods; (4) who is making supplemental feeding decisions; and (5) if there are geographical differences among supplementation choices and reasons for supplementation. Methods: An exploratory, descriptive, cross sectional survey of IBCLCs was conducted to generate data about their use of supplemental feeding methods. The survey was sent via email invitation through the International Board of Lactation Consultant’s Board of Examiners, with a response rate of 11.5% (N = 2,308). Results: There was no standard method of supplementation among participants. Participants indicated that they were confident advising mothers on alternative feeding methods. Only 17.6% (n = 406) of participants reported that the IBCLC was the caregiver who recommended the method of supplementation used. The majority of participants believed the Supplemental Feeding Tube Device SFTD) best preserves the breastfeeding relationship, and this was their preferred method of supplementation. However, the bottle was ranked as the number one method used in the United States, Australia, and Canada. The use of alternative feeding methods may be overwhelming to the mother. Conclusion: Supplementation by alternative feeding methods might help preserve the breastfeeding relationship and help reach the World Health Organization’s goal of increasing exclusive breastfeeding rates. © The Author(s) 2019.
4 citations (Crossref) [2023-10-31] Citation Key Alias: pop00187 tex.type: [object Object]
Keywords: *Breast Feeding/sn [Statistics & Numerical Data]; *Consultants; *Infant Formula/sn [Statistics & Numerical Data]; *Practice Patterns; Nurses'; Adult; Breast Feeding; Certification; Consultants; Cross-Sectional Studies; Female; Global Health; Humans; Infant Formula; Infant; Newborn; International Board Certified Lactation Consultant; Middle Aged; Postnatal Care; Practice Patterns; Nurses'; Pregnancy; Surveys and Questionnaires; Young Adult; adult; artificial feeding; artificial milk; breast feeding; breastfeeding support; certification; consultation; cross-sectional study; dept.nur; female; global health; human; middle aged; newborn; nursing practice; peer-reviewed; postnatal care; pregnancy; questionnaire; supplementation; young adult

Workplace incivility: Nurse leaders as change agents - Green, Cheryl Ann (Nursing Management, 2019)
An abstract is unavailable.
7 citations (Crossref) [2023-10-31]
Keywords: Humans; Interprofessional Relations; Leadership; Nursing Staff; Organizational Innovation; Workplace; dept.nur; human; leadership; nursing staff; organization; peer-reviewed; public relations; workplace

Bereavement care to minimize bereaved parents' suffering in their lifelong journey towards healing - Denhup, Christine (Applied Nursing Research, 2019)
This article presents select findings from an interpretive phenomenological study which aimed to describe the lived experience of parental bereavement. Six parents, each of whom experienced the death of a child due to cancer at least one year prior, participated in conversational interviews to share what it has been like for them since their child's death. Heideggerian (1962) phenomenology provided the philosophical underpinnings of the study, while van Manen's (1997) phenomenological method guided data collection and analysis. From this methodological approach, a structure of the meaning of parental bereavement experience was revealed. Profound suffering emerged as one essential theme. Pertinent findings related to this theme are discussed. Parents share ways others might minimize their suffering and provide support in their lifelong journey towards healing. Findings will enhance nurses' practice of providing bereavement care, which is an expectation of quality palliative care. Copyright © 2019 Elsevier Inc. All rights reserved.
12 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/134-579-857-152-025 tex.type: [object Object]
Keywords: *Adaptation; Psychological; *Bereavement; *Neoplasms/mo [Mortality]; *Nurse's Role/px [Psychology]; *Nursing Staff; Hospital/px [Psychology]; *Parents/px [Psychology]; *Stress; Psychological/px [Psychology]; Adaptation; Psychological; Adult; Attitude to Death; Bereavement; Child death; Female; Humans; Male; Middle Aged; Neoplasms; Nurse's Role; Nursing Staff; Hospital; Palliative care; Parental bereavement; Parents; Stress; Psychological; Suffering; adult; attitude to death; bereavement; child parent relation; coping behavior; dept.nur; female; human; male; mental stress; middle aged; mortality; neoplasm; nurse attitude; nursing staff; peer-reviewed; psychology

Orientation Learning Needs of Adjunct Clinical Faculty in the United States - Sousa, Monica P.; Resha, Cheryl A. (Nursing Education Perspectives, 2019)
Aim: The aim of the study was to examine the orientation learning needs of adjunct clinical faculty as they transition from expert clinicians to novice educators. Background: Schools of nursing are increasingly using adjunct clinical faculty because of the nurse faculty shortage. Retention is a concern. Method: This descriptive quantitative study used the Needs Assessment Survey for Topic Inclusion in a Guide to Orientation. Adjunct clinical faculty rated the level of importance of orientation topics and if they received needed information. Results: The majority of topics were found to be rated very important or important. Several items deemed very important or important were either not discussed or not sufficiently discussed in orientation. Conclusion: The information obtained demonstrates the vast amount of information that adjunct clinical faculty want and need in an orientation. © 2019 Lippincott Williams & Wilkins.
2 citations (Crossref) [2023-10-31]
Keywords: Adjunct Clinical Faculty; Clinical Nurse Faculty; Clinical Teaching; Faculty Orientation; Faculty; Nursing; Humans; Needs Assessment; Nurses; Transition Into Academia; United States; article; clinical education; clinician; dept.nur; human; learning; needs assessment; nurse; nursing education; peer-reviewed; quantitative analysis

Preventing and alleviating compassion fatigue through self-care: An educational workshop for nurses - Adimando, Andrea (Journal of Holistic Nursing, 2018)
Though various authors have refined and described the concept of compassion fatigue (CF), the overarching features, predisposing factors, and potential consequences remain relatively consistent. Available literature demonstrates that caregivers caring for patients who are chronically ill and/or traumatized are at highest risk for developing CF. Potential consequences for unmitigated CF include physical, emotional, and work-related consequences, all of which can have negative effects on the quality and safety of care and degree of engagement with one’s employer. CF is further exacerbated by exposure to cumulative, unresolved stress and neglect of one’s own emotional needs over time. Caregivers must be knowledgeable on CF’s risk factors, symptoms, and management strategies to decrease its incidence and negative impacts. This article details the creation, execution, and evaluation of an evidence-based practice change project implemented with the goal of increasing knowledge needed to prevent, identify, and alleviate CF in high-risk nurses. The project involved a series of educational workshops containing information on CF’s risk factors, symptoms, and consequences, with a strong emphasis on self-awareness, self-care, and stress management. Pre- and postknowledge tests showed a significant increase in knowledge was achieved via the workshops, and qualitative surveys indicated a high level of participant satisfaction with the program contents, format, and impact.
21 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/110-914-713-725-562, pop00211 tex.type: [object Object]
Keywords: Adult; Burnout; Professional; Compassion Fatigue; Female; Holistic Nursing; Humans; Inservice Training; Male; Middle Aged; Nurses; Quality of Life; Self Care; Surveys and Questionnaires; adult; burnout; caring; compassion fatigue; dept.nur; educators; female; grief/loss/suffering; health and wellness coaching; holistic nursing; human; in service training; male; meditation/mindfulness; middle aged; nurse; nurses; peer-reviewed; prevention and control; psychology; quality of life; questionnaire; self care; stress and coping; stress management/relaxation; trauma/posttrauma

Peaches and crocs: A story of gratitude for nurses - Resha, Cheryl Ann (American Nurse Today: Insights, 2018)
My story began when I was 49 years young and told I had Stage IV colorectal cancer. That was almost 12 years ago, and today I am one of the fortunate ones—not only has it been almost 12 more years of living, but my oncologist has used the word “cured”. Like most cancer patients and …
Keywords: dept.nur; ⛔ No DOI found

Cup Feeding as a Supplemental, Alternative Feeding Method for Preterm Breastfed Infants: An Integrative Review. - Penny, Frances; Judge, Michelle; Brownell, Elizabeth; McGrath, Jacqueline M (Maternal and child health journal, 2018)
Background The benefits of human milk for the preterm infant are well established. Preterm infants have lower breastfeeding rates and often face breastfeeding challenges. It is important that feeding practices for preterm infants optimize their chances of breastfeeding. Objective The purpose of this integrated review is to synthesize and critically analyze research related to the safety and efficacy of cup feeding as an alternative, supplemental feeding method for breastfed infants. Data Sources The electronic data bases of PubMed, CINAHL and were used to identify studies published in English from 1998- 2017. Design Using inclusion and exclusion criteria, 27 articles were initially assessed. After further screening 19 articles were included in the full review and of these 5 more were excluded. Lastly, an in-depth review of these 14 studies resulted in 2 more exclusions, for a total of 12 studies that met full inclusion and exclusion criteria. Review Methods Studies were examined for information on safety and efficacy of cup feeding as an alternative, supplemental feeding method for preterm breastfed infants. Studies were grouped into categories of outcomes that included (a) safety and physiologic properties; (b) breastfeeding outcomes. Results Use of cup feeding resulted in more stable heart rate and oxygen saturation than bottle feeding with similar weight gain. Additionally, breastfeeding rates were higher at discharge with continued higher rates at 3 and 6 months post-discharge for cup fed infants. Conclusions Premature infants face more breastfeeding obstacles than term infants. The potential for cup feeding as an alternative to bottle-feeding for breast fed preterm infants is positively supported by these results It is fundamentally important for NICU professionals to establish a protocol, education and training for the potential use of this feeding method for this vulnerable population.
13 citations (Crossref) [2023-10-31] Place: United States Penny, Frances. Department of Nursing, Southern Connecticut State University, 501 Crescent Street, New Haven, CT, 06515, USA. Pennyf1@southernct.edu. Penny, Frances. School of Nursing, University of Connecticut, Storrs, CT, USA. Pennyf1@southernct.edu. Judge, Michelle. School of Nursing, University of Connecticut, Storrs, CT, USA. Brownell, Elizabeth. Connecticut Children's Medical Center, Hartford, CT, USA. Brownell, Elizabeth. School of Medicine, University of Connecticut, Farmington, CT, USA. McGrath, Jacqueline M. School of Nursing, University of Connecticut, Storrs, CT, USA. McGrath, Jacqueline M. Connecticut Children's Medical Center, Hartford, CT, USA.
Keywords: *Bottle Feeding; *Breast Feeding/mt [Methods]; *Cooking and Eating Utensils; *Enteral Nutrition/mt [Methods]; *Feeding Methods; *Infant; Premature/ph [Physiology]; Alternative feeding; Bottle Feeding; Breast Feeding; Breastfeeding; Cooking and Eating Utensils; Cup feeding; Enteral Nutrition; Enteral Nutrition/is [Instrumentation]; Feeding Methods; Female; Humans; Infant; Newborn; Infant; Premature; Infants; Male; Preterm; bottle feeding; breast feeding; dept.nur; devices; enteric feeding; female; food intake; human; kitchen; male; newborn; peer-reviewed; physiology; prematurity; procedures

Incivility among nursing professionals in clinical and academic environments: emerging research and opportunities - Green, Cheryl (IGI Global, 2018)
Traditionally, nursing is acknowledged as a caring profession and is associated with advocating for others. However, incivility is increasingly occurring amongst nurses, both in the clinical and academic environments, and is causing affected nurses both psychological and physical harm. Incivility Among Nursing Professionals in Clinical and Academic Environments: Emerging Research and Opportunities provides emerging views and consequences surrounding workplace bullying in the healthcare profession including recognizing the signs and symptoms of incivility in the workplace, identifying ways in which affected nurses can seek help, and examining healthy methods of coping with the incivility. Featuring coverage on a broad range of topics such as human resources, therapy, and clinical nursing, this book is ideally designed for nurses, managers, healthcare workers and consumers, hospital and clinical staff, researchers, students, and policymakers.
Citation Key Alias: greenIncivilityNursingProfessionals2019, lens.org/024-055-981-898-128, pop00327
Keywords: dept.nur

Using case study methodology to explore the role of discrimination in workplace incivility - Green, Cheryl (Journal of National Black Nurses' Association: JNBNA, 2018)
Exclusionary behaviors can be detrimental to the health and well-being of faculty in the workplace. When colleagues are judged by their peers because of the color of their skin, the language they speak, their gender, or who they choose to love (lesbian, gay, bisexual, transgender, asexual, or questioning), affected faculty are left emotionally and physically vulnerable. Institutions of higher learning must set standards of zero tolerance for faculty-to-faculty incivility. With standards taken from each faculty discipline, codes of conduct can be implemented not only at a departmental level, but also throughout the educational system.
Keywords: Discrimination; Exclusionary; Faculty; Humans; Incivility; Interprofessional Relations; Prejudice; dept.nur; peer-reviewed

Complimentary Care: When Our Patients Request to Pray. - Green, Cheryl Ann (Journal of Religion and Health, 2018)
Prayer is viewed in modern medicine as a complimentary alternative treatment. However, to many patients, it is a source of hope and comfort. Patients, when facing illness, advanced disease, disability or death, can benefit from prayer. For healthcare providers, comfort with praying with patients can be deemed as unprofessional conduct or blurred therapeutic boundaries, particularly, when prayer is offered to patients' unsolicited by the patient or their family member(s). Therefore, it is imperative that healthcare providers await the request of prayer by the patient before prayer is initiated.
5 citations (Crossref) [2023-10-31] Place: United States Green, Cheryl Ann. Southern Connecticut State University, 501 Crescent Street, Jennings Hall, Office 121, New Haven, CT, 06515, USA. Greenc16@southernct.edu.
Keywords: *Attitude of Health Personnel; *Delivery of Health Care; *Faith Healing; *Pastoral Care/mt [Methods]; *Religion; *Spirituality; Attitude of Health Personnel; Delivery of Health Care; Faith Healing; Family; Healthcare providers; Humans; Nurse's Role; Nurses; Pastoral Care; Patients; Prayer; Religion; Religion and Medicine; Spirituality; dept.nur; family; health care delivery; health personnel attitude; human; nurse attitude; pastoral care; peer-reviewed; procedures; religion; spiritual healing

Contemporary issues: The pre-licensure nursing student and medication errors. - Green, Cheryl (Nurse Education Today, 2018)
In Modern health care, the creation of cultures of safety for patients is of the upmost importance. Impacting the institutional stabilization of health care facilities safety initiatives, is the preparation of pre-licensure nursing students to safely administer medications to patients. Therefore, preparation of the pre-licensure nursing student must be evidence-based practice focused and incorporate innovative ways to reduce the potential for medication errors. Copyright © 2018. Published by Elsevier Ltd.
8 citations (Crossref) [2023-10-31] Place: Scotland Green, Cheryl. Southern Connecticut State University, Department of Nursing, Jennings Hall Office 121, United States. Electronic address: Greenc16@southernct.edu.
Keywords: *Clinical Competence; *Medication Errors/nu [Nursing]; *Students; Nursing; Clinical Competence; Education; Nursing; Baccalaureate; Humans; Licensure; Nursing; Medication Errors; Medication Errors/pc [Prevention & Control]; Medication errors; Pre-licensure nursing students; Prevention; Students; Nursing; adult; clinical competence; dept.nur; drug safety; editorial; evidence based practice center; health care facility; human; licensing; medication error; nursing; nursing education; nursing student; peer-reviewed; prevention and control

Using instrumentation in psychiatric nursing to assess documentation of the nursing process for emergent non-psychiatric patient events. - Green, Cheryl (Archives of Psychiatric Nursing, 2018)
Ongoing education of experienced psychiatric nurses is imperative given the historically complex health presentations of psychiatric patients. Psychiatric patients tend to have medical co-morbidities and often do not have the financial resources for preventative health care. The hospitalization for acute psychiatric stabilization, is an opportunity for psychiatric nurses to teach and advocate for patients' physiological and psychological health. Documentation of patients' changes in condition and overall clinical presentation, is necessary to ensure patients' health care needs are met. Copyright © 2018 Elsevier Inc. All rights reserved.
0 citations (Crossref) [2023-10-31] Place: United States Green, Cheryl. Southern Connecticut State University, Department of Nursing, Jennings Hall, Office 121, New Haven, CT 06515, United States; Yale-New Haven Psychiatric Hospital, New Haven, CT 06510, United States. Electronic address: Greenc16@southernct.edu.
Keywords: *Documentation/st [Standards]; *Inservice Training/mt [Methods]; *Nursing Process; *Psychiatric Nursing; Documentation; Educational Measurement; Educational Measurement/sn [Statistics & Numerical Data]; Hospitalization; Humans; Inservice Training; Nurses; Nursing Process; Nursing process; Patients; Psychiatric Nursing; Psychiatry; Surveys and Questionnaires; adult; article; comorbidity; dept.nur; documentation; education; health care need; hospitalization; human; in service training; mental patient; nurse; nursing process; peer-reviewed; procedures; psychiatric nursing; psychological well-being; questionnaire; standards; statistics and numerical data

New nursing faculty and incivility: applying mindfulness-based strategies - Green, Cheryl (Holistic Nursing Practice, 2018)
Workplace incivility remains a problem within the nursing profession. As nurse leaders, we must recognize and not ignore the complexity of cultures that have adapted incivility into the work environment. Nursing education is a discipline that requires collaborative team work, independent drive, and commitment. New nursing faculty experiencing incivility can use mindfulness-based meditation approaches to cope with uncivil behaviors experienced within the workplace. Nurse educators applying the concepts of mindfulness can learn how to provide themselves self-care by reducing stress, as enhanced daily awareness of peace and calm are incorporated into their lifestyle. Mindfulness provides a realization that control can only be given to other persons when an individual allows or accepts another's negative behaviors. Awareness of the value and importance of oneself can assist the nurse educator experiencing incivility to maintain his or her emotional, physical, and spiritual health despite the volatility of the work environment.
9 citations (Crossref) [2023-10-31] tex.eissn: 1550-5138 tex.unique-id: ISI:000417936200002
Keywords: Attitude of Health Personnel; Bullying; Faculty; Nursing; Humans; Incivility; Interprofessional Relations; Mindfulness; Stress; Psychological; Universities; Workplace; academia; adult; awareness; bullying; complication; dept.nur; etiology; female; health personnel attitude; human; human experiment; incivility; leadership; lifestyle; male; meditation; mental stress; mindfulness; nursing education; nursing faculty; occupation; organization and management; peer-reviewed; psychology; public relations; self care; standards; stress; teamwork; trends; university; work environment; workplace

What is the evidence for use of a supplemental feeding tube device as an alternative supplemental feeding method for breastfed infants? - Penny, Frances; Judge, Michelle; Brownell, Elizabeth; McGrath, Jacqueline M. (Advances in Neonatal Care, 2018)
Background: According to the Healthy People 2020 goals, the sustainability of breastfeeding duration rates within the United States has not been achieved. To increase these rates, it is important that women with breastfeeding difficulties receive the support needed to continue breastfeeding. When supplementation occurs, it is essential that the breastfeeding relationship be preserved. Various methods of supplementation are often recommended including use of the supplemental feeding tube device (SFTD). Purpose: The question guiding this brief is “What evidence exists to support the use of an SFTD as a method of supplementation for breastfed infants?” Search Strategy: The PubMed and CINAHL databases were queried for original research published in English from 1990 through July 2016. Search terms included “supplemental feeding tube,” “breastfeeding,” “term infants,” “premature infants,” “Supplemental Nursing System,” “Lact-aid,” and “supply line.” Findings: Very limited research exists on the use of SFTDs as a method of supplementation for breastfed infants; however, existing research suggests that an SFTD may be useful as a supplementation method for breastfed infants. High-quality research is needed to evaluate the efficacy of using an SFTD for supporting exclusive and all breastfeeding rates. Implications for Practice: Nurses and providers need to be educated and trained in the use of SFTDs as well as all supplemental feeding methods. Information on efficacy and SFTD use should also be included in policies related to breastfeeding and human milk use. Implications for Research: Further research should determine best methods of supplementation for breastfed infants and should examine differences in breastfeeding rates when using the SFTD for supplementation.
10 citations (Crossref) [2023-10-31] tex.eissn: 1536-0911 tex.unique-id: ISI:000426548300007
Keywords: Breast Feeding; Breastfeeding; Dietary Supplements; Enteral Nutrition; Humans; Infant; Newborn; Nursing Care; Treatment Outcome; breast feeding; breastfeeding support; breastmilk; dept.nur; dietary supplement; enteric feeding; human; human milk; newborn; newborn intensive care; nursing care; peer-reviewed; preterm infant; procedures; supplemental feeding; supplemental feeding device; treatment outcome

Evaluation of the McMahon Competence Assessment Instrument for use with midwifery students during a simulated shoulder dystocia - McMahon, Erin; Jevitt, Cecilia; Aronson, Barbara (Journal of Midwifery & Women's Health, 2018)
IntroductionIntrapartum emergencies occur infrequently but require a prompt and competent response from the midwife to prevent morbidity and mortality of the woman, fetus, and newborn. Simulation provides the opportunity for student midwives to develop competence in a safe environment. The purpose of this study was to determine the inter-rater reliability of the McMahon Competence Assessment Instrument (MCAI) for use with student midwives during a simulated shoulder dystocia scenario. MethodsA pilot study using a nonprobability convenience sample was used to evaluate the MCAI. Content validity indices were calculated for the individual items and the overall instrument using data from a panel of expert reviewers. Fourteen student midwives consented to be video recorded while participating in a simulated shoulder dystocia scenario. Three faculty raters used the MCAI to evaluate the student performance. These quantitative data were used to determine the inter-rater reliability of the MCAI. ResultsThe intraclass correlation coefficient (ICC) was used to assess the inter-rater reliability of MCAI scores between 2 or more raters. The ICC was 0.86 (95% confidence interval, 0.60-0.96). Fleiss's kappa was calculated to determine the inter-rater reliability for individual items. Twenty-three of the 42 items corresponded to excellent strength of agreement. DiscussionThis study demonstrates a method to determine the inter-rater reliability of a competence assessment instrument to be used with student midwives. Data produced by this study were used to revise and improve the instrument. Additional research will further document the inter-rater reliability and can be used to determine changes in student competence. Valid and reliable methods of assessment will encourage the use of simulation to efficiently develop the competence of student midwives.
1 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000428796300010 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.researcherid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: Article; Clinical Competence; Dystocia; Education; Nursing; Educational Measurement; Female; Humans; Infant; Newborn; McMahon Competence Assessment Instrument; Midwifery; Nurse Midwives; Observer Variation; Pilot Projects; Pregnancy; Reproducibility of Results; Shoulder; Simulation Training; Video Recording; assessment; clinical competence; competence; content validity; controlled study; correlation coefficient; dept.nur; dystocia; education; evaluation; expert system; female; human; instrument; intrarater reliability; midwife; midwifery education; midwifery student; newborn; nurse midwife; nursing education; observer variation; obstetric procedure; peer-reviewed; pilot study; pregnancy; priority journal; procedures; quantitative analysis; quantitative study; reliability; reproducibility; scoring system; shoulder; shoulder dystocia; simulation; simulation training; standards; teacher; validation study; validity; videorecording

The elderly and the opioid epidemic: A case study - Green, Cheryl A. (Addictive Disorders & Their Treatment, 2017)
Opioid addiction is a problem within the United States that is impacting all age groups. The elderly are a population that is seldom discussed as being affected by opioids. Physiologically, the older adult is more susceptible for complications associated with an alteration in pharmacokinetics and late diagnosis of diseases such as viral hepatitis C. Health promotion for this population is imperative in the prevention and treatment of opioid addiction problems.
1 citations (Crossref) [2023-10-31]
Keywords: Article; Hepatitis C virus; United States; aged; boceprevir; buprenorphine plus naloxone; case report; clinical article; creatinine; creatinine blood level; dept.nur; diamorphine; follow up; health care personnel; health promotion; hepatitis C; human; male; medicare; methadone; methadone treatment; older adults; opiate addiction; opioids; oxycodone; priority journal; protein blood level; self report; telaprevir; urea nitrogen blood level; weight reduction

Examining school-aged youth - Adimando, Andrea (Legal Resources for School Health Services, 2017)
A comprehensive resource that addresses the legal issues regarding school health services for school nurses, school administrators and school attorneys. Over 50 topics are included including information on federal laws, compliance, medication administration, professional licensure and malpractice, minor rights and mental health and much more. Over 70 authors include school nurse experts, and education and nurse attorneys. Each chapter is evidence based and peer reviewed by both school nurse content experts and attorneys. Responds to questions submitted by school nurses and school administrators. A reference that will support school nurse and school health practice, enhance care to children and provide guidance to protect the school and school nurse.
Keywords: dept.nur

The process for delegation in the school setting - Resha, Cheryl Ann (Legal Resources for School Health Services, 2017)
A comprehensive resource that addresses the legal issues regarding school health services for school nurses, school administrators and school attorneys. Over 50 topics are included including information on federal laws, compliance, medication administration, professional licensure and malpractice, minor rights and mental health and much more. Over 70 authors include school nurse experts, and education and nurse attorneys. Each chapter is evidence based and peer reviewed by both school nurse content experts and attorneys. Responds to questions submitted by school nurses and school administrators. A reference that will support school nurse and school health practice, enhance care to children and provide guidance to protect the school and school nurse.
Keywords: dept.nur

Technology use and technological self-efficacy among undergraduate nursing faculty - Roney, Linda N.; Westrick, Susan J.; Acri, Mary C.; Aronson, Barbara S.; Rebeschi, Lisa M. (Nursing Education Perspectives (Wolters Kluwer Health), 2017)
AIM This study explored faculty responses to a survey about using technology to teach undergraduate nursing students. BACKGROUND Little is known regarding faculty confidence, technology use, or supports for integrating technology into nursing education. METHOD A descriptive correlational design was utilized to explore the relationship between technology use and technological self-efficacy in faculty (N = 272) who teach at Commission on Collegiate Nursing Education–accredited nursing programs. Instruments used were a sociodemographic questionnaire, the Roney Technology Use Scale, and the Technology Self-Efficacy Scale. RESULTS Participants who taught didactic content had moderate technology use as compared to those teaching didactic and clinical/laboratory who reported high levels of technology use. A weak relationship between age and technological self-efficacy (ρ =.127, p < .05) was also found. CONLUSION This research was an initial step in understanding levels of technology use and responses to this challenge by undergraduate nursing faculty.
10 citations (Crossref) [2023-10-31] Citation Key Alias: roneyTechnologyUseTechnological2017a
Keywords: Adult; Bivariate Statistics; Coefficient Alpha; Computer Assisted Instruction; Computer Literacy; Confidence; Confidence Intervals; Content Validity; Correlational Studies; Data Analysis Software; Descriptive Research; Descriptive Statistics; Education Research; Education; Nursing; Baccalaureate; Educational Status; Educational Technology – Utilization; Faculty Development; Faculty Practice; Faculty; Nursing; Female; Human; Male; Middle Age; Nonexperimental Studies; Nurse Faculty; Nursing Education; P-Value; Promotion and Tenure; Questionnaires; Scales; Schools; Nursing; Self-Efficacy; Socioeconomic Factors; Students; Nursing; Baccalaureate; Summated Rating Scaling; Surveys; T-Tests; Teaching Methods; Technological Self-Efficacy; Technology; adult; age; article; clinical laboratory; controlled study; dept.nur; dept.swk; female; human; human experiment; major clinical study; male; nursing education; nursing student; peer-reviewed; questionnaire; self concept; teaching

Nursing students' access to test banks: are your tests secure? - Madara, Bernadette; Resha, Cheryl; Krol, Maria D.; Lacey, Kimberly; Martin, Elaine F.; O'Sullivan, Cynthia; Smith, Jan Weingrad (Journal of Nursing Education, 2017)
Background: Schools of nursing have moved to multiple choice test questions to help prepare students for licensure and practice. However, students can buy test banks to help them “get through” nursing school. Accurate assessment of nursing students' knowledge and judgment comprises access to test banks. Method: The purpose of this exploratory study was to gain an understanding about nursing faculty's knowledge concerning test bank security issues, to assess whether publishers were aware of this issue, and vendor's reasons for supplying test banks to students. Results: Overall, the results indicated that the majority of faculty were unaware of student access to test banks, and although most do not use test banks verbatim, general consensus existed that test bank security is a concern. Conclusion: Implications include increasing faculty awareness of test bank access by students, supporting educators to develop their own test bank items, and promoting security of all examinations.
6 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000402479200008 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Attitude of Health Personnel; Commerce; Databases as Topic; Education; Nursing; Educational Measurement; Faculty; Nursing; Humans; Internet; Surveys and Questionnaires; awareness; commercial phenomena; consensus; data base; dept.nur; education; exploratory research; health personnel attitude; human; human experiment; nursing; nursing education; questionnaire; student; university

Epidemiology in community health care - Jung, Betty C. (Community & Public Health Nursing: Promoting the Public's Health, 2017)
Help your students understand that community/public health nursing skills benefit their nursing practice as well as patient outcomes in acute care This student-friendly, highly visual text expands students’ viewpoints from the client-nurse relationship to a population focus. Acknowledging that population-focused tools and interventions are needed in acute care, as infection rates continue to rise and nurse-sensitive outcome indictors are closely monitored, Cherie Rector weaves in meaningful, real-life examples, case studies, and perspectives to help students understand that transitions in care are critical in today’s healthcare system. Covering a multitude of community and public settings, situations, and populations, the book helps students learn about promoting health, preventing disease (not just treating it), and protecting at-risk populations—including the elderly, the LGBT community, and veterans. This fully updated 9th Edition encourages students to think more globally and covers new innovations and emerging threats to the public’s health.KEY FEATURESNEW! QSEN sections tie key chapter concepts to quality and safety competencies, such as patient-centered care, teamwork & collaboration, evidence-based practice, quality improvement, and informatics, to help students understand the importance of these concepts.NEW! Application to Population Health explores chapter concepts from a population-focused viewpoint and offers current examples of effective population interventions.What Do YOU Think? encourages students to reflect on thought-provoking current topics or dilemmas, enhancing critical thinking skills.Evidence-based Practice demonstrates how current research examples can be applied to public/community health nursing practice to achieve optimal outcomes.From the Case Files presents case study scenarios with application-based questions, challenging students to reflect on assessment and intervention.Perspectives from nursing students, novice to expert public health nurses, faculty members, policy makers, and clients cover commonly held misconceptions about community health nursing and link between skills across settings.Healthy People 2020 highlights pertinent goals and objectives to promote health.Activities to Promote Critical Thinking at the end of each chapter challenge students, promote critical-thinking skills, and encourage active involvement in solving community health problems.Unique Levels of Prevention Pyramid boxes address a chapter topic and describe nursing actions at each of the three levels of prevention to help students understand this basic community health nursing concept. Content from the text is embedded into two integrated digital learning solutions— Lippincott CoursePoint for pre-licensure programs and Lippincott RN to BSN Online for post-licensure programs—that feature experiential, case-based instructional design aligned with the approach of the Ninth Edition. To learn more about Lippincott CoursePoint and Lippincott RN to BSN Online and to see our Video Cases, please visit http://nursingeducationsuccess.com.
Keywords: dept.nur

A new state of being: the lived experience of parental bereavement - Denhup, Christine Yvonne (OMEGA - Journal of Death and Dying, 2017)
In spite of growing bereavement literature, the meaning of the lived experience of parental bereavement is not well understood. This article presents selected findings from a Heideggerian hermeneutic phenomenological study which aimed to describe the lived experience of bereaved parents who experienced the death of a child due to cancer. Conversational interviews were conducted with six parents who experienced the death of a young child due to cancer at least one year prior to participation. The nature of parental bereavement was revealed to be a new state of being into which parents enter immediately after the death of a child and which has no end point. Findings will equip health professionals and others who work with bereaved parents with a deeper understanding of the meaning of parental bereavement.
15 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000391796100004 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Adult; Bereavement; Child; Child; Preschool; Death; Female; Humans; Male; Models; Psychological; Neoplasms; Parents; Pediatric Nursing; adult; bereavement; child; child death; death; dept.nur; female; hermeneutic phenomenology; human; male; neoplasm; parent; parental bereavement; pediatric nursing; preschool child; psychological model; psychology

Town & gown: Building successful university-community partnerships - King, Beth M.; Gordon, Shirley C.; Barry, Charlotte D.; Goodman, Rhonda; Jannone, Laura T.; Foley, Marie; Resha, Cheryl; Hendershot, Candace (NASN School Nurse, 2017)
1 citations (Crossref) [2023-10-31]
Keywords: dept.nur

School nurse guidelines for: Developmental disabilities - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Enuresis - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Fifth disease (erythema infectiosum) - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Homelessness - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Human Papillomavirus (HPV) - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Life Threatening cardiac conditions, (Long QT intervals and hypertrophic cardiomyopathy) - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Mental health - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Service animals - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Suicide - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Teen pregnancy - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

After the gap analysis: Education and practice changes to prepare nurses of the future - Beauvais, Audrey Marie; Kazer, Meredith Wallace; Aronson, Barbara; Conlon, Suzanne E.; Forte, Pamela; Fries, Kathleen S.; Hahn, Judith M.; Hullstrung, Russell; Levvis, Meg; McCauley, Paula; Morgan, Patricia Padula; Perfetto, Linda; et al. (Nursing Education Perspectives, 2017)
AIM The purpose of the study was to describe the Connecticut Nursing Collaborative-Action Coalition’s work in identifying and addressing gaps between nursing education and practice based on the Institute of Medicine’s Future of Nursing report. BACKGROUND Massachusetts Nurse of the Future (NOF) Competencies highlight the knowledge, skills, and attitudes/behaviors required for professional nurses. Integrating these concepts into the educational system will prepare the nursing workforce to respond to current/future health care needs and population health issues. METHOD Education and practice partners in four regions conducted a gap analysis of the education to practice transition for new graduate nurses using NOF as a framework for assessment. RESULTS Gaps in competencies were similar across regions. However, each organization uniquely addressed curricular gaps to best prepare nurses of the future. CONCLUSION Curriculum improvements will provide students the advantage of being prepared for the rapid changes happening in health care. Copyright © 2017 National League for Nursing
4 citations (Crossref) [2023-10-31]
Keywords: Academic-Practice Partnership; Connecticut; Curriculum; Education; Nursing; Forecasting; Future of Nursing Competencies; Gap Analysis; Humans; Massachusetts; New Graduate Nurses; Nursing Curriculum; Nursing Education; Nursing Staff; article; curriculum; dept.nur; forecasting; health care need; human; human experiment; nursing education; nursing staff; peer-reviewed; population health; skill; student; workforce

School nurse guidelines for: Abdomen-blunt injury - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Abdominal pain / appendicitis - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Abrasions - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Bed bugs - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Bipolar disorder - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Child abuse - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur

School nurse guidelines for: Cytomegalovirus (CMV) - Towle, Antoinette (Legal resource for school health services, 2017)
Keywords: dept.nur